Colorimetric and Fluorescent Dual-Modality Sensing Platform Based on Fluorescent Nanozyme - Wan, Yejian; Zhao, Jingwen; Deng, Xiaochun; Chen, Jie; Xi, Fengna; Wang, Xiaobo (Frontiers in Chemistry, 2021)
Comparing to natural enzymes, nanozymes based on carbonaceous nanomaterials are advantages due to high stability, good biocompatibility, and possibility of multifunctionalities through materials engineering at atomic level. Herein, we present a sensing platform using nitrogen doped graphene quantum dot (NGQD) as highly efficient fluorescent peroxidase mimic, which enable colorimetric/fluorescent dual-modality platform for detection of hydrogen peroxide (H2O2) and biomolecules (ascorbic acid-AA, acid phosphatase-ACP) with high sensitivity. NGQD is synthesized using a simple hydrothermal process, which has advantages of high production yield and potential for large-scale preparation. NGQD with uniform size (3.0 nm ± 0.6 nm) and single-layer graphene structure exhibits bright and stable fluorescence. N-doping and ultrasmall size endow NGQD with high peroxidase-mimicking activity with obviously reduced Michaelis-Menten constant (Km) in comparison with natural horseradish peroxidase (HRP). Taking advantages of both high nanozyme activity and unique fluorescence property of NGQD, a colorimetric and fluorescent dual-modality platform capable of detecting H2O2 and biomolecules (AA, ACP) with high sensitivity is developed as the proof-of-concept demonstrations. Furthermore, the mechanisms underlying the nanozyme activity and biosensing are investigated.